Teachers' Opinion Regarding Teacher Evaluation in Undergraduate Medical Education (Bangladesh Journal of Medical Education, 2017)
This descriptive type of cross-sectional study was conducted to find out the teachers' opinion about teacher evaluation in undergraduate medical education at two government and three non-government medical colleges in Dhaka city by convenience sampling. 30 teachers were participated and they were from Assistant Professor to Professor Level. Teachers gave their opinion about potential use, facilities, barriers and factors affecting the implementation of teacher evaluation through in-depth interview. Majority of teachers opined that a well developed teacher evaluation system is a must in undergraduate medical education. It is strongly felt by the participant teachers that teacher evaluation has presently become very much essential against the backdrop of continuous changing of curriculum, technology, teaching styles, pattern of society, disease demography etc. Teachers agreed that it can improve teaching ability and protect students from incompetent teachers. Most of the teachers agreed about the necessity of student involvement in the teacher evaluation programme. Problem if arise can be resolved by implementing teacher evaluation with the help of a precise or proper guideline from policy level. Study recommended that teacher evaluation should start from undergraduate medical college. Study also mentioned that teachers' classroom performance and relationship with students should be used as parameters of teacher evaluation. In conclusion it can be said that without teacher evaluation there is no way for quality improvement of teacher and undergraduate medical education.Bangladesh Journal of Medical Education Vol.6(1) 2015: 12-18